2018
DOI: 10.1111/and.12953
|View full text |Cite
|
Sign up to set email alerts
|

DNAH6is a novel candidate gene associated with sperm head anomaly

Abstract: Globozoospermia and acephalic spermatozoa are two rare sperm head anomalies associated with male infertility. Combination of the two phenotypes in the same patient is extremely rare, so the underlying pathogenesis of this disorder remains unclear. Here, we report a 35-year-old infertile male, who presented with 30% of sperm-lacked heads and 69% of sperm round-headed or small-headed with neck thickening in his ejaculate. Subsequent whole-exome sequencing (WES) analysis identified compound heterozygous variants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 27 publications
1
41
0
1
Order By: Relevance
“…Previous studies have shown that dynein axonemal heavy chain 6 (DNAH6) is involved in generating the force required for ciliary beating, and mutations in this gene may cause primary ciliary dyskinesia, non-obstructive azoospermia, or sperm morphological defects [ 8 11 ]. By using a high-resolution array comparative genomic hybridization platform, a 171 kb deletion in DNAH6 was identified as the main etiology of POI in a patient [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that dynein axonemal heavy chain 6 (DNAH6) is involved in generating the force required for ciliary beating, and mutations in this gene may cause primary ciliary dyskinesia, non-obstructive azoospermia, or sperm morphological defects [ 8 11 ]. By using a high-resolution array comparative genomic hybridization platform, a 171 kb deletion in DNAH6 was identified as the main etiology of POI in a patient [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other dynein proteins had been associated with spermatozoa function and morphology, including DNAH6 , DNAAF3 , and DNAL1 (Li et al., 2016, ; Mazor et al., ; Mitchison et al., ). Of these, mutations in DNAH6 and DNAAF3 have been noted in patients with spermatozoa characterized by abnormal flagella, reduced motility, and defective dynein.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in several central pair complex and radial spoke head proteins have been identified in PCD patients. For patients with mutations in the C2 central pair projection gene HYDIN, infertility has been reported in affected men [59,91]. Subfertility caused by sperm motility defects have also been reported for male PCD patients with mutations in the radial spoke genes DNAJB13 (DnaJ heat shock protein family (Hsp40) member B13), RSPH3 (radial spoke head 3 homolog) and RSPH9 [13,27,37,48,62].…”
Section: The Effect Of Pcd Mutations In Dynein Arm Assembly Genes Andmentioning
confidence: 99%